SEKULARISME HUKUM DALAM FRAME TIMUR DAN BARAT - Azmi Abu Bakar (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2017)
Until now a western philosophical school called secularism has become an inseparable part of Islamic scholars. Related article cited a variety of secularism and the note that also take as a reference by the next generation of scientific. This fact shows that the importance of the discussion concerning matters of secularism.Position secularism became a big spotlight when linked to Islamic law an sich. Harassment of Islamic law through the glass secularism has produced many Islamic intellectuals secular.In fact, the West itself slowly began to abandon secularism. Western consciousness leaving the methodology of secularism marked by the rise of Islamic hegemony slowly, even predicted the future of Islam will be the largest religion in Western Europe represent entities. The position of Islam itself is still vulnerable to the methodology of secularism. Post-figure Kemal in Turkey proklaimed himself as a successful carrier of secularism which is then followed by other Muslim intellectuals. This makes the Islamic intellectual dilemma. As if, methodology of secularism could raise the degree of religious and linked well with the sects that emerged in the mid such Mu'tazilah. Secularism eventually become a new color in Islam, secularism began to force its philosophy in Islam. Define secularism as the separation of religion and state effort was apparently not enough. Abstrak: Hingga kini sebuah aliran filsafat Barat yang bernama sekularisme telah menjadi bagian yang tak bisa dipisahkan dari para cendekiawan Islam. Berbagai tulisan terkait sekularisme dikutip kemudian tulisan itu diambil pula sebagai rujukan oleh para generasi ilmiyah lintas zaman. Kenyataan ini menunjukkan bahwa betapa pentingnya pembahasan menyangkut hal ihwal sekularisme. Posisi sekularisme menjadi sorotan besar manakala dikaitkan dengan hukum Islam an sich. Pengobok-obokan hukum Islam melalui kaca sekularisme telah melahirkan banyak intelektual Islam bermanhaj sekuler.Pada kenyataannya, Barat sendiri mulai meninggalkan sekularisme secara perlahan. Kesadaran Barat meninggalkan manhaj sekularisme ditandai dengan munculnya hegemoni Islam secara perlahan, bahkan kedepan diprediksi Islam akan menjadi agama terbesar di Eropa mewakili entitas Barat.Posisi Islam sendiri sampai saat ini masih rentan dengan manhaj sekularisme. Paska tokoh Kemal di Turki memploklamasikan dirinya sebagai pembawa sekularisme sukses yang kemudian diikuti pula oleh para intelektual Islam lainnya. Hal ini menjadikan para intelektual Islam dilematis. Seolah-olah, manhaj sekularisme bisa menaikkan derajat beragama lalu dikait-kaitkan pula dengan sekte-sekte yang muncul di era pertengahan semisal muktazilah.Sekularisme akhirnya menjadi warna baru dalam Islam, filsafat sekularisme mulai dipaksakan dalam ajaran Islam. Mendefiniskan sekularisme sebagai upaya pemisahan agama dan negara rupanya belumlah cukup. Kata Kunci: Sekularisme, agama, dunia, Barat